2022
DOI: 10.37256/amtt.3220221766
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Bacterial and Fungal Spoilage Organisms in Branded and Unbranded Milk; Consumer Perception of Safety Hazard for Milk

Abstract: Background: This research aims to isolate and identify bacterial and fungal spoilage organisms in branded and unbranded milk, as well as to assess the parameters linked to milk safety risk. A total of 30 samples were collected for laboratory testing. For analysis, the samples were inoculated on several mediums. The bacterial and fungal isolates were identified using Gram staining and biochemical identification methods. Results: According to the findings, Klebsiella spp. and Escherichia coli are the most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The increase in acidity may be due to the production of microbial metabolic products such as acetic acid and lactic acid in coconut milk (Kurwijila, 1997). Lactic, acetic and succinic acids at concentration below 1.2 g/L, are being produced during the fermentation of coconut milk by Lactobacillus reuteri LR 92 (Onoharigho et al, 2022). However, coconut milk fermented by Lactobacillus reuteri DSM 17938, showed higher production of lactic acid (5.45 ± 0.33 g/L) and acetic acid in a lower proportion (0.56 ± 0.08 g/L) (Mauro & Garcia, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in acidity may be due to the production of microbial metabolic products such as acetic acid and lactic acid in coconut milk (Kurwijila, 1997). Lactic, acetic and succinic acids at concentration below 1.2 g/L, are being produced during the fermentation of coconut milk by Lactobacillus reuteri LR 92 (Onoharigho et al, 2022). However, coconut milk fermented by Lactobacillus reuteri DSM 17938, showed higher production of lactic acid (5.45 ± 0.33 g/L) and acetic acid in a lower proportion (0.56 ± 0.08 g/L) (Mauro & Garcia, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Coliform organisms and fungi such as Penicillium, Geotricum, Mucor, Fusarium and Saccharomyces spp. are also commonly found in coconut milk (Onoharigho et al, 2022). The generation time for multiplication of bacterial cells in coconut milk drops from 232 min at 10 °C to 44 min at 30 °C (Vallath & Shanmugam, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Sugars, proteins, fats, and nucleic acids all benefit from the stimulation provided by these antioxidants. This stimulation leads to cellular changes that eventually trigger an antioxidant response [110]. There is significant antioxidant action in honey.…”
Section: Antioxidant Activity Of Honeymentioning
confidence: 99%
“…The antioxidant qualities of honey may be quantified by testing its ability to scavenge free radicals using assays including the oxygen radical absorbance capacity (ORAC) assay, the 1,1diphenyl-2-picrylhydrazyl (DPPH) scavenging assay and the ferric reducing antioxidant power (FRAP) assay (Escriche et al, 2014). High antioxidant capabilities in honey have been said to vary depending on the floral variety and region (Onoharigho et al, 2022). Honey (1.2 g/kg) was in a certain study shown to increase beta-carotene, vitamin C, glutathione reductase, uric acid levels and antioxidant activity in healthy adult volunteers Geană et al (2020).…”
Section: Antioxidant Activitymentioning
confidence: 99%